The Effect of Both Earnings Management and Tax Planning To The Value of The Company With Corporate Governance As Variable Moderating - Nia Suryani; Djuminah Djuminah (AFEBI Accounting Review, 2017)
The primary objective of this study is to determine the impact of both earnings management and tax planning towards the value of the firm, corporate governance is measured by using score CGPI as moderating variable. This study uses purposive sampling method that generates 40 samples of company listings on the Indonesia Stock Exchange (IDX) and registered in participation Corporate Governance Perception Index (CGPI) during 2012 until 2015.Based on the test result of regression analysis it showed that earnings management practices which is measured by using discretionary accrual shows regression coefficients of 2,557 with p-value of 0,015 or p-value is below 0,05, so it has negative impact to the value of the firm, then it can be concluded that the existence of earnings management can reduce the value of the firm. Tax planning activity is measured by using Cash_ETR which shows regression coefficients -0.956 with a p-value of 0,005 or p-value is below 0,05, which means it gives a negative impact to the value of the firm, so it can be concluded that the higher level of tax planning by management will have an impact on the declining value of the firm. Furthermore, corporate governance which is measured using the CGPI’s score is not a moderating variable between earnings management and value of the firm, showed by p-value of 0,090, whereas the relationships of tax planning and value of the firm can be moderated by corporate governance, showed by p-value of 0,024.Keywords: CGPI’s Score, Corporate Governance, Discretionary Accrual, Earnings Management, Tax Planning, Value of the Firm